Preparation method of metal sulfide graphene roll lithium ion battery negative electrode material
Patent Information
- Application Number
- CN202410281807.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-13
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-13
AI Technical Summary
[0004]本发明的目的为针对目前金属硫化物负极材料所面临的低电导率、体积膨胀严重等问题,提供了一种金属硫化物石墨烯卷锂离子电池负极材料的制备方法
前期的发明专利中,对于金属硫化物与石墨烯复合材料的制备通常涉及杂质的去除,合成过程较为繁琐,并且传统的一锅水热法结合高温煅烧对于复合材料的纳米结构难以实现有效调控,这使得金属硫化物负极材料本身的优势难以充分发挥。
Smart Images

Figure CN118062897B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy storage materials, specifically the development of a method for preparing a metal sulfide graphene-coated lithium-ion battery anode material. Background Technology
[0002] With the widespread adoption and development of home appliances, electronic products, and aerospace facilities, designing and using innovative energy storage systems with excellent cycle stability and high power / energy density has become crucial. Graphite, as a common commercial lithium-ion battery anode material, possesses advantages such as chemical stability, a low charge / discharge potential plateau, and minimal volume expansion. However, graphite has a relatively low theoretical specific capacity of only 372 mA hg. -1 Metal sulfides such as SnS2, MoS2, and MnS possess high theoretical capacity and abundance, while their lower battery voltage effectively reduces energy loss. Furthermore, compared to oxides, metal sulfides exhibit higher electrochemical reactivity and reversibility due to their weaker metal-sulfur bonds. However, their low conductivity and slow reaction kinetics hinder their full capacity utilization, resulting in poor rate performance. Additionally, electrode material pulverization and collapse caused by volume changes during cycling also lead to severe capacity decay. Composite with graphene is an effective method to address the problems of metal sulfide anodes. The addition of graphene can significantly improve the material's conductivity and ion transfer efficiency, while also increasing its structural stability.
[0003] Previous synthesis methods mainly involved first synthesizing composite materials of metal sulfides and graphene nanosheets through hydrothermal or co-precipitation methods. For example, patent CN109659544A proposed a hydrothermal reaction combined with high-temperature calcination to synthesize transition metal sulfide / graphene composite materials. However, this preparation method usually uses inorganic metal salts as raw materials, so impurities need to be removed after the initial hydrothermal reaction, which increases the complexity of the preparation. At the same time, the control over the nanostructure of the composite material and the ratio between metal sulfides and graphene is poor. Summary of the Invention
[0004] The purpose of this invention is to address the problems of low conductivity and severe volume expansion faced by current metal sulfide anode materials by providing a method for preparing a metal sulfide@graphene nanofiber lithium-ion battery anode material. This invention uses a decomposable organometallic salt as the metal source for sulfide preparation. A mixed dispersion of graphene oxide and the metal salt is obtained through electrostatic bonding. This dispersion is then subjected to freeze-drying and high-temperature sulfidation to obtain a metal sulfide@graphene nanofiber heterostructure lithium-ion battery anode material. This invention eliminates the need for a purification process, and the resulting composite material has a conductivity of 0.2 A g. -1 The reversible specific capacity reaches 1610 mA hg after 200 cycles at a current density.-1 .
[0005] The technical solution of this invention is: A method for preparing a metal sulfide graphene-coated lithium-ion battery anode material, the method comprising the following steps: (1) Add organometallic salt and polyvinylpyrrolidone (PVP) to deionized water and stir at room temperature for 0.1-1 h to obtain mixed solution A; The mass ratio of organometallic salt to PVP is 1:0.1~2; 0.1~2.0 g of organometallic salt is added to every 10~100 mL of deionized water. The organometal salts mentioned are stannous acetate (Sn(CH3COO)2), manganese acetate (Mn(CH3COO)2), or ammonium molybdate (NH4)2MoO4. (2) Preparation of graphene oxide dispersion: The dried graphene oxide was ultrasonically dispersed in deionized water to obtain GO dispersion, which is denoted as dispersion B. The mass concentration of the GO dispersion was 0.1–8 mg / mL. -1 ; (3) Add dispersion B dropwise to mixed solution A and stir at room temperature for 10~90 min to obtain a mixed dispersion of metal salt and graphene oxide; Among them, the ratio of organometallic salt to GO (mass ratio) is 10:0.1~4; The volume ratio of mixed solution A to dispersion B is 1:1~10; (4) Freeze-drying: The mixed dispersion obtained in (3) is placed in liquid nitrogen and frozen, and then placed in a freeze dryer for freeze-drying for 1~84h to obtain the dried solid product; (5) High-temperature sulfidation: The first ceramic boat containing thiourea is placed at the front end of the tube furnace, and the second ceramic boat containing the solid product obtained in step (4) is placed at the rear end of the tube furnace. After heat treatment at 300~500 °C for 1~5 hours under inert atmosphere protection, the metal sulfide graphene roll lithium-ion battery anode material is finally obtained.
[0006] The ratio of the freeze-dried solid product to thiourea (mass ratio) is 1:1~10. The graphene oxide in step (2) is graphene oxide prepared by the improved Hummers method.
[0007] The inert gas mentioned is argon; The application of the metal sulfide graphene roll lithium-ion battery anode material prepared by the method is as a negative electrode sheet for lithium-ion batteries. The process includes the following steps: mixing the electrode material obtained in (5) with conductive carbon and binder at a mass ratio of 8:1:1 to obtain a mixed material; adding deionized water and stirring at room temperature for 6-24 h; after stirring, uniformly coating the resulting suspension onto copper foil with a coating amount of 0.5-2 mg / cm² per unit area. -2 The negative electrode sheet for lithium-ion batteries is obtained by vacuum drying at 80~120 ℃ for 10~20 h. Add 50-250 mg of the mixed material per 600-1000 µL of deionized water; The binder is sodium carboxymethyl cellulose, and the conductive carbon is Super P.
[0008] The positive electrode of the lithium-ion battery is a lithium metal sheet, the separator is a glass fiber membrane, and the electrolyte is 1.0 mol / L. -1 A solution of LiPF6 in a mixture of dimethyl carbonate (DMC), methyl ethyl carbonate (EMC), and ethylene carbonate (EC) in a volume ratio of 1:1:1.
[0009] The essential features of this invention are: In previous invention patents, the preparation of metal sulfide and graphene composite materials usually involved the removal of impurities, and the synthesis process was quite complicated. Furthermore, the traditional one-pot hydrothermal method combined with high-temperature calcination made it difficult to effectively control the nanostructure of the composite material, which made it difficult to fully utilize the advantages of the metal sulfide anode material itself.
[0010] This invention uses easily decomposable organometallic salts and thiourea as metal and sulfur sources, respectively, and graphene nanorolls as a conductive substrate. Through the electrostatic bonding between metal ions and graphene oxide (GO) nanosheets, the organometallic salts are adsorbed onto the GO surface as "seeds." After freeze-drying, a few layers of GO nanosheets spontaneously curl, anchoring the metal salts onto the GO nanorolls. Finally, high-temperature vulcanization yields a metal sulfide@graphene nanoroll heterostructure composite material. The inventors discovered that this freeze-drying combined with high-temperature vulcanization strategy results in uniformly attached metal sulfides onto the graphene nanorolls, effectively improving the material's electronic conductivity and mitigating volume expansion during charging and discharging. The heterostructure interface between the curled graphene and the metal sulfide enhances ion diffusion efficiency, while the hollow nanostructure of the graphene nanorolls better accommodates the volume changes of the metal sulfide during lithium storage, further increasing the material's structural stability.
[0011] The beneficial effects of this invention are as follows: (1) This invention uses decomposable organometal salts as metal sources and adsorbs the metal salts onto the surface of GO nanosheets through electrostatic interaction, thus creating conditions for the preparation of metal sulfide composite materials. (2) In this invention, the two-dimensional GO nanosheets are made to self-roll by freeze-drying using the ice template method. The dried organometallic salt can be uniformly attached to the surface of the GO nanosheets. This preparation process does not require any impurity removal steps, the operation is simple, the experimental conditions are mild, and it is suitable for large-scale production. (3) In this invention, organometallic salts and graphene oxide are used as reaction starters, and thiourea is used as the sulfur source for the sulfidation reaction. These raw materials are low in cost and low in pollution. Furthermore, the ratio of metal sulfides to graphene nanorolls in the composite material can be directly adjusted by changing the addition ratio of the raw materials. (4) The in-situ growth of metal sulfide nanoparticles on the surface of graphene nanorolls was achieved by high-temperature sulfidation. At the same time, the hydrogen sulfide gas generated by thiourea at high temperature can dop S into the carbon skeleton of graphene, further improving the conductivity. (5) The SnS2@graphene nanoroll heterostructure anode material prepared under optimal conditions in this experiment was obtained at 0.2 A g. -1 The reversible specific capacity reaches 1590 mA hg after 200 cycles. -1 ; (6) When this method was applied to the preparation of other metal sulfide and graphene nanoroll composite materials, it showed good lithium storage performance, which provides strong evidence for the commercial application of this method in the field of energy storage materials. Attached Figure Description
[0012] Figure 1 This is a scanning electron microscope image of the SnS2@graphene nanoroll composite material in Example 1; Figure 2 The X-ray diffraction pattern of the SnS2@graphene nanoroll composite material in Example 1 is shown below. Figure 3 The SnS2@graphene nanoroll composite material in Example 1 was used at 0.2 A g. -1 Cyclic performance at current density; Figure 4 The SnS2@graphene nanoroll composite material in Example 1 at 1 A g -1 Cyclic performance at current density; Figure 5 This is a rate performance diagram of the SnS2@graphene nanoroll composite material in Example 1; Figure 6 The SnS2@graphene nanoroll-1 composite material in Example 2 was tested at 0.2 A g. -1 Cyclic performance at current density; Figure 7 The SnS2@graphene nanoroll-2 composite material in Example 3 was tested at 0.2 A g. -1Cyclic performance at current density; Figure 8 This is a scanning electron microscope image of the MoS2@graphene nanoroll composite material in Example 4; Figure 9 The XRD test curve of the MoS2@graphene nanoroll composite material in Example 4 is shown. Figure 10 In Example 4, the MoS2@graphene nanofiber composite material was used at 0.2 A g. -1 Cyclic performance at current density; Figure 11 This is a scanning electron microscope image of the MnS@graphene nanoroll composite material in Example 5.
[0013] Figure 12 The XRD test curve of the MnS@graphene nanoroll composite material in Example 5; Figure 13 The MnS@graphene nanoroll composite material in Example 5 was tested at 0.2 A g. -1 Cyclic performance at current density. Detailed Implementation
[0014] This invention first dissolves an organometallic salt and the surfactant PVP in deionized water to obtain a homogeneous organometallic salt solution, which is then mixed with a graphene oxide dispersion. Following freeze-drying and high-temperature sulfidation, a metal sulfide@graphene nanoroll heterostructure composite material is finally obtained. This material exhibits high reversible specific capacity and excellent rate performance. This novel preparation method of the metal sulfide-graphene nanoroll heterostructure anode material lays the foundation for the application of high-performance metal sulfide anode materials in the field of energy storage.
[0015] Example 1 Add 0.356 g stannous acetate and 0.150 g PVP to 35 mL of deionized water and stir at room temperature for 0.5 h to obtain a homogeneous solution, denoted as solution A; prepare 35 mL of graphene oxide (GO-based on the modified Hummers method, document number: Journal of Alloys and Compounds 862 (2021) 158472) dispersion (1.0 mg / mL). -1Dispersion B was added dropwise to solution A, and stirring was continued for 0.5 h to obtain a mixed dispersion of metal salt and graphene oxide. The solution was transferred to a petri dish and rapidly frozen with liquid nitrogen (to prevent agglomeration of the dispersion and thus the formation of graphene nanorolls). After complete freezing, the solution was freeze-dried at -30°C for 72 h to obtain a solid product with a mass of 0.55 g. The obtained product was placed in a ceramic boat and positioned at the rear end of a tube furnace. 4 g of thiourea was weighed and poured into another ceramic boat, which was then placed at the front end of the tube furnace. The furnace was then heated in an argon atmosphere (at a rate of 120 mL / min from front to back). -1 Under the protection of a flow rate purging, the SnS2 composite material (SnS2@graphene nanorolls) was heat-treated at 500 °C for 3 h at a heating rate of 10 °C / min to obtain SnS2 composite material (SnS2@graphene nanorolls) grown in situ on graphene nanorolls. The obtained SnS2@graphene nanoroll composite material was uniformly mixed with conductive carbon (Super P) and binder (sodium carboxymethyl cellulose) at a mass ratio of 8:1:1 (total amount of 125 mg) to obtain SnS2@graphene nanoroll mixed material. 800 µL of deionized water was added, and the mixture was stirred at room temperature for 12 h. After stirring, the obtained SnS2@graphene nanoroll mixed material suspension was uniformly coated onto copper foil (approximately 1 mg coating per square centimeter of copper foil) and vacuum dried at 100 °C for 12 h. The resulting electrode sheet was cut into 12 mm diameter circular pieces using a manual slicer to obtain the negative electrode sheet. In this embodiment, the battery adopts a standard half-cell configuration, with a CR2025 stainless steel coin cell casing, a lithium foil as the counter electrode, Celgard 2500 as the separator, and a 1 M LiPF6 mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) (volume ratio 1:1:1). The voltage range for this test is 0.01~3 V, and the test current is 0.2 A g. -1 The test was conducted using the LAND CT2001A battery testing system.
[0016] Figure 1 This is a scanning electron microscope image of the SnS2@graphene nanorolls in Example 1. The image shows that tin disulfide is uniformly attached to the graphene in layers without obvious agglomeration, and the graphene sheets exhibit a rolled-up structure, forming an interconnected network structure in the material.
[0017] Figure 2 The image shows the XRD curve of SnS2@graphene nanorolls in Example 1. It shows a tin disulfide crystal structure. No obvious graphene characteristic diffraction peaks were observed in the figure. This is because the diffraction peaks of tin disulfide are strong, thus obscuring the peaks of graphene.
[0018] Figure 3For SnS2@graphene nanoroll composite materials at 0.2 A g -1 Cycling performance at current density. The discharge and charge specific capacities of this composite material in the first cycle are 1514 and 1325 mA hg, respectively. -1 The initial coulombic efficiency reached 88%, and the reversible specific capacity after 200 cycles reached 1610 mA hg. -1 The Coulomb efficiency is close to 100%.
[0019] Figure 4 For SnS2@graphene nanoroll composite materials in 1 A g -1 Cyclic performance at current density. The reversible specific capacity of this composite material reaches 1003 mA hg after 900 cycles. -1 The Coulomb efficiency is close to 100%.
[0020] Figure 5 This is a rate performance diagram of the SnS2@graphene nanoroll composite material. The composite material at 10 A g... -1 and 20 Ag -1 The reversible specific capacity at the current density reached 853 mA hg. -1 and 508 mA hg -1 This indicates its excellent rate performance.
[0021] Example 2 The steps are the same as in Example 1, except that the mass of stannous acetate added to dispersion A is changed to 0.119 g, and other conditions remain unchanged. The resulting composite material is denoted as SnS2@graphene nanoroll-1.
[0022] Figure 6 0.2 A g of SnS2@graphene nanoroll-1 composite material -1 The cycling performance diagram shows that the discharge and charge specific capacities of this composite material in the first cycle are 1124 and 943 mA hg, respectively. -1 The reversible specific capacity reached 1083 mA hg after 200 cycles. -1 .
[0023] Example 3 The steps are the same as in Example 1, except that the mass of stannous acetate added to dispersion A is changed to 0.474 g, and other conditions remain unchanged. The resulting composite material is denoted as SnS2@graphene nanoroll-2. Figure 7 For SnS2@graphene nanoroll-2 composite materials at 0.2 A g -1 Cycling performance at current density. The discharge and charge specific capacities of this composite material in the first cycle are 1494 and 1263 mA hg, respectively.-1 The reversible specific capacity reaches 1080 mA hg after 200 cycles. -1 The Coulomb efficiency is close to 100%.
[0024] Example 4 The steps are the same as in Example 1, except that the stannous acetate added to dispersion A is replaced with ammonium molybdate, with an added mass of 0.294 g. Other conditions remain unchanged, and the resulting composite material is denoted as MoS2@graphene nanoroll. Figure 8 This is a scanning electron microscope image of the MoS2@graphene nanoroll composite material, in which MoS2 nanoparticles grown on the surface of the graphene nanorolls can be observed. Figure 9 XRD patterns of MoS2@graphene nanorolls. Figure 10 The graph shows the cycling performance of the MoS2@graphene nanoroll composite material. The discharge and charge specific capacities of this composite material during the first cycle are 1130 and 978 mA hg, respectively. -1 The reversible specific capacity after 100 cycles reaches 1233 mA hg. -1 The Coulomb efficiency is close to 100%.
[0025] Example 5 Simply replace the stannous acetate added to dispersion A with manganese acetate at a mass of 0.260 g, keeping other conditions unchanged, and the resulting composite material will be denoted as MnS@graphene nanorolls. Figure 11 This is a scanning electron microscope image of MnS@graphene nanorolls, showing MnS growing on the surface of the graphene nanorolls. Figure 12 The XRD pattern of MnS@graphene nanorolls is shown. Figure 13 The graph shows the cycling performance of the MnS@graphene nanoroll composite material. The discharge and charge specific capacities of this composite material during the first cycle are 1261 and 897 mA hg, respectively. -1 The reversible specific capacity reaches 888 mA hg after 100 cycles. -1 The Coulomb efficiency is close to 100%.
[0026] As can be seen from the above embodiments, the product of the present invention uses decomposable organometallic salts and thiourea as the metal source and sulfur source, respectively. Through electrostatic adsorption and freeze-drying, the metal salts are uniformly attached to graphene oxide nanorolls. High-temperature sulfidation then achieves in-situ growth of metal sulfides on the graphene nanorolls. The carbon content in the product can be precisely controlled by adjusting the proportion of metal salts added, without the need for intermediate impurity removal. The rolled-up graphene improves the conductivity of the material and effectively alleviates volume expansion. The heterostructure formed by the alternating metal sulfides and graphene nanorolls greatly enhances the charge transfer efficiency of the material, achieving a comprehensive improvement in the lithium storage performance of the composite material.
[0027] Matters not covered in this invention are common knowledge.
Claims
1. A method for preparing a metal sulfide graphene-coated lithium-ion battery anode material, characterized in that the method includes the following steps: (1) Add organometallic salt and polyvinylpyrrolidone (PVP) to deionized water and stir at room temperature for 0.1-1 h to obtain mixed solution A; in, The mass ratio of organometallic salt to PVP is 1:0.1~2; add 0.1~2.0 g of organometallic salt per 10~100 mL of deionized water; The organometal salt is stannous acetate, manganese acetate, or ammonium molybdate; (2) Preparation of graphene oxide dispersion: Graphene oxide was ultrasonically dispersed in deionized water to obtain GO dispersion, denoted as dispersion B; The mass concentration of the GO dispersion was 0.1–8 mg / mL. -1 ; (3) Add dispersion B dropwise to mixed solution A and stir at room temperature for 10~90 min to obtain a mixed dispersion of metal salt and graphene oxide; The mass ratio is organometallic salt:GO = 10:0.1~4; (4) Freeze-drying: The mixed dispersion obtained in (3) is placed in liquid nitrogen and frozen, and then placed in a freeze dryer for freeze-drying for 1~84h to obtain the dried solid product; (5) High-temperature sulfidation: The first ceramic boat containing thiourea is placed at the front end of the tube furnace, and the second ceramic boat containing the solid product obtained in step (4) is placed at the rear end of the tube furnace. After heat treatment at 300~500 °C for 1~5 hours under inert atmosphere protection, the metal sulfide graphene roll lithium-ion battery anode material is finally obtained. The mass ratio of the freeze-dried solid product to thiourea is 1:1~10. The volume ratio of mixed solution A to dispersion B is 1:1~10; The graphene oxide in step (2) is graphene oxide prepared by the modified Hummers method; The inert gas mentioned is argon.
2. The application of the metal sulfide graphene roll lithium-ion battery anode material prepared by the method described in claim 1, characterized in that it is used as the anode sheet of a lithium-ion battery.
3. The application as described in claim 2, characterized in that: Includes the following steps: The electrode material obtained in (5) was mixed with conductive carbon and binder at a mass ratio of 8:1:1 to obtain a mixed material. Deionized water was added, and the mixture was stirred at room temperature for 6-24 h. After stirring, the resulting suspension was uniformly coated onto copper foil, with a coating amount of 0.5-2 mg / cm² per unit area. -2 The negative electrode sheet for lithium-ion batteries is obtained by vacuum drying at 80~120℃ for 10~20 h. Add 50-250 mg of the mixed material per 600-1000 µL of deionized water; The binder is sodium carboxymethyl cellulose, and the conductive carbon is Super P.
4. The application as described in claim 2, characterized in that the positive electrode of the lithium-ion battery is a metallic lithium sheet, the separator is a glass fiber membrane, and the electrolyte is 1.0 mol / L. -1 A solution of LiPF6 in a mixture of dimethyl carbonate, methyl ethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1.
Citation Information
Patent Citations
Preparation method of lithium / sodium ion battery anode material of graphene coated bimetallic sulfide
CN109659544A
Graphene / metal oxide composite nanomaterial, preparation method and application thereof, electrode plate and application thereof
CN114784227A